William Ospina, I Will Put My Ear on the Stone Until It Speaks. Literatura Random House, 2023, 358 pages - López-González, Rosendo; Ramírez-Valencia, Astrid (Visión electrónica, 2024)
William Ospina, Pondré mi oído en la piedra hasta que hable. Random House, 2023, 358 páginas